Formulation Development and Characterization of Self-Emulsifying Drug Delivery System (SEDDS) of Glibenclamide for Enhanced Solubility and Stability (International Journal of Scientific Research in Science and Technology, 2024)
Glibenclamide, a widely prescribed oral hypoglycemic agent, suffers from poor aqueous solubility and variable bioavailability, which limit its therapeutic efficacy. The present study aimed to develop and characterize a self-emulsifying drug delivery system (SEDDS) of Glibenclamide to improve its solubility and stability. Various oils, surfactants, and co-surfactants were screened for maximum solubility of Glibenclamide. Pseudo-ternary phase diagrams were constructed to identify the optimal region of self-emulsification. The optimized SEDDS formulation was characterized for droplet size, zeta potential, emulsification time, thermodynamic stability, drug content, and in-vitro dissolution. Results demonstrated that the optimized SEDDS achieved rapid emulsification (<60 s), produced nano-sized globules (<150 nm), and significantly improved the dissolution rate compared to pure Glibenclamide. Stability studies confirmed that the formulation remained stable under accelerated storage conditions for three months. Thus, SEDDS represents a promising strategy to enhance the solubility and stability of Glibenclamide for improved therapeutic outcomes.